Dalit Consciousness and Voice of Resistance in Pabitra Sunar’s Yugako Āwāj - Charmakar, Rudra Bahadur (Pursuits: A Journal of English Studies, 2024)
The article explores how Nepali literature written on Dalit subjects and issues portrays the socio-cultural, political and economic disparity and injustice experienced by Dalits; and, how the literature expresses dissatisfaction, resistance and protest against it. The article basically aims to explore Dalit consciousness and voice of resistance expressed in poems. For this purpose, the researcher has studied Pabitra Sunar’s anthology of poems “Yugako Āwāj [Voice of the Era] from the concept of class consciousness connecting with Dalit consciousness. Her poems mainly express the agony, pain, suffering, inequality, injustice, discrimination, exploitation and oppression; and, also expresses hope, expectation and revolt for rights, equality, justice, freedom and dignity of Dalits. Fundamentally, the poems portray Nepalese society, socio-cultural, political and economic status of Dalits, and, present the right path for socio-cultural liberation of Dalits. The poems also plea the entire Dalits to revolt against caste system for overall transformation. Moreover, the binary appositions such as pessimism and optimism, dark and light, rejection and acceptance, fear and braveness, discrimination and equality faced by Dalits in society; and, Dalits’ wish for liberation and dignity are the tenets in Sunar’s poems. The researcher has adopted qualitative approach with explorative and analytical methods while studying the poems.